Notes on the Vertebrates of northern Pará, Brazil: a forgotten part of the Guianan Region, III. A new species of Microcaecilia (Amphibia: Gymnophiona: Caeciliidae) - Maciel, Adriano Oliveira; Hoogmoed, Marinus Steven (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2011)
A new species of Microcaecilia is described from the municipality of Óbidos, state of Pará, in the Brazilian part of the Guianan Region. The new species has a high number of secondary annuli, monocuspid vomeropalatine teeth, and other characteristics that together differentiate it from the other eight known species of the genus.
Keywords: Brazil; Guianan Region; Gymnophiona; Microcaecilia; New species